ACCREDITATION OF THE EDUCATIONAL PROGRAM OF A HIGHER EDUCATION INSTITUTION AS AN ADMINISTRATIVE PROCEDURE - Legenkyi, Mykola (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to analyze the scientific-theoretical, methodological-organizational and regulatory support for the accreditation of an educational program of a higher education institution as an administrative procedure. Research methods: comparative, analytical-synthetic, comparativist, generalization and systematization. Results: the relevance of the accreditation of an educational program of a higher education institution as a significant factor in ensuring the quality of educational services and the quality of education in general is substantiated, an analysis and generalization of international experience in ensuring quality through the use of accreditation procedures is carried out, accreditation is studied in the status of an administrative procedure, which requires additional scientific and legislative support. Discussion: it was found that studies of the regulatory and legal regulation of the accreditation procedure in higher education in other countries indicate a strong experience gained in this direction, which is characterized by unity in confirming the high relevance of accreditation procedures and general approaches to their implementation, which are characterized by the ramifications of the system of entities providing accreditation services and certain differences in its time dimension and purpose. It was determined that the main features of the administrative procedure, which include normalization, publicity and subjectivity, phasing and sequence of actions, as well as the adoption of authoritative management decisions through the exercise of the powers of officials, can be fully attributed to the accreditation of educational programs. It was proven that the studies of administrative scientists substantiate the status of accreditation of educational programs as an administrative procedure that has a dispositive nature and is used as a tool of public administration of higher education provision. At the same time, the normalization of the above-mentioned status requires additional scientific and legislative support and careful development of the procedure for its implementation.